Masked Hypotension due to Elevated Venous Pressure in a Patient with Complex Adult Congenital Heart Disease - Wytch Rigger; Sean P. Javaheri; Gyanendra K. Sharma; Norris Stanley Nahman; Mark Sheynshteyn; Neal L. Weintraub (Case Reports in Cardiology)
An adult with surgically corrected Tetralogy of Fallot presented with profoundly elevated central venous pressure (CVP) and acute renal dysfunction thought secondary to acute on chronic right heart failure. Treatment with dopamine promoted diuresis and a stabilization of renal function. Repeated attempts to wean the patient from dopamine were associated with hypotension and worsening renal failure. Invasive hemodynamic assessment unexpectedly demonstrated high cardiac output with low systemic vascular resistance (SVR). In retrospect, the markedly elevated CVP had concealed the impact of reduced SVR on blood pressure. After reversible causes of low SVR state were excluded, the patient was successfully managed with oral alpha-adrenergic agents. While typically negligible under physiologic conditions, elevated CVP can artificially increase mean arterial pressure. We have coined the term “masked hypotension” to describe this unique pathophysiological phenomenon.